Development of Digital Comic Media to Cultivate Students' Attitude of Cooperation in Civics Subjects in Class VS D Negeri 133889 Tanjung Medan - Desfira Sari Rezeky (Berpusi Publishing, 2026)
This study aims to develop digital comic media that can foster students' cooperative attitudes in the PPKn subject in grade V of SD Negeri 133889 Tanjung Medan. This research is motivated by the low level of student engagement in group work activities and the use of conventional learning media, which makes it less interesting for students. This study uses the Research Method. and Development (R&D) with a 4D development model that includes the define , design , development , and disseminate stages . The research subjects were 25 fifth-grade students of SD Negeri 133889 Tanjung Medan. The research instruments used included validation sheets from material experts, media experts, and linguists, as well as teacher and student response questionnaires to determine the level of practicality of the media. The results of the study showed that the developed digital comic media met the criteria of very valid and very practical. This was indicated by the results of the material expert validation of 92%, the media design expert validation of 100%, and the linguist validation of 100% with the very valid category. In addition, the results of the practicality test showed that the teacher's response obtained a percentage of 94% with the very practical category, while the student's response obtained a percentage of 90% with the very practical category. Based on these results, it can be concluded that the developed digital comic media is suitable for use as a learning medium in the PPKn subject for fifth-grade elementary schools and is able to help foster students' cooperative attitudes in the learning process.